Hookah Use Among Adolescents in the United States: Results of a National Survey. Issue 2 (23rd October 2013) - Amrock, Stephen M.; Gordon, Terry; Zelikoff, Judith T.; Weitzman, Michael
Abstract: Introduction: U.S. adolescents increasingly use alternative tobacco products (ATPs), including hookah. No study has previously assessed correlates of adolescent hookah use in a nationally representative sample. Methods: Cross-sectional, nationally representative data of adolescents from the 2011 National Youth Tobacco Survey (NYTS) were used. Student demographics and their use of, exposure to, and beliefs about tobacco were examined as correlates of hookah use. Results: Of adolescents nationwide, 7.3% reported ever trying hookah and 2.6% reported using hookah within the past month. Increasing age was associated with trying hookah, but not current hookah use. Sex was unassociated with hookah use. Asians were most likely to have tried hookah; Hispanics and those of another race reported greater current hookah use. Hookah use increased with perceived ease of access to and willingness to try tobacco. Students with a hookah user at home were more likely to have tried hookah and to currently use hookah. Current cigarette use was not associated with current hookah use (odds ratio [ OR ] = 1.3, 95% CI = 0.8–2.1), but was associated with trying hookah ( OR = 1.5, 95% CI = 1.1–2.2). Non-cigarette tobacco use was associated with trying hookah ( OR = 2.7, 95% CI = 2.1–3.5) and current hookah use ( OR = 4.8, 95% CI = 2.7–8.7). Conclusions: A sizeable minority of U.S. adolescents use hookah, particularly those living with hookah users, those who use other ATPs, and those who perceive tobacco as easily accessible. Current cigarette use was not associated with current hookah use. Future studies assessing the dangers of hookah use and interventions to curb this emerging problem appear warranted.